2019
DOI: 10.4018/ijpada.2019100102
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Radio Frequency Identification in Libraries

Abstract: Nowadays, RFID technology is widely being used in libraries across the world. This study is in line with global literature pertaining to the implementation of RFID technology in libraries and intends to explore and examine the perceptions of employees from two libraries in Qatar. Data was collected from both staff and managers using two separate surveys. The perceptions of both sets of employees were analyzed and compared to highlight the differences in benefits, drawbacks, and issues concerning the implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Finally, significant differences between managers and employees' perspectives were reported. Later Ganapathi and Abu-Shanab (2019) replicated the study in Qatar, where they explored employees' perceptions in this regard in the library of Qatar University and Qatar National Library. Results concluded that shelf management of resources, perceived RFID contributions, and workplace efficiency were the top rated dimensions pertaining to the use of RFID.…”
Section: Iot Uses and Applications In Traffic Sourcementioning
confidence: 97%
“…Finally, significant differences between managers and employees' perspectives were reported. Later Ganapathi and Abu-Shanab (2019) replicated the study in Qatar, where they explored employees' perceptions in this regard in the library of Qatar University and Qatar National Library. Results concluded that shelf management of resources, perceived RFID contributions, and workplace efficiency were the top rated dimensions pertaining to the use of RFID.…”
Section: Iot Uses and Applications In Traffic Sourcementioning
confidence: 97%